The child's right to be heard: a normative and jurisprudential study in Ecuador - Tulcanaza Chávez, Gennyth Patricia (2025)
In Ecuadorian legal proceedings involving minors, a problem arises that has received little attention: the distinction between the right to be heard and the mere act of hearing them. The main objective of this paper is to address this issue through a critical analysis from a national and conventional legal perspective. A qualitative method was used to compile and analyze primary sources, applying techniques such as the compilation of specialized bibliography, analysis, and summarization. Legal hermeneutics was used as the method for analyzing the regulations. As a result, it was possible to determine the differences between hearing and listening to minors in legal proceedings involving them. It concludes that there is an imminent need for judges to consider parameters in the administration of justice, thereby guaranteeing the rights of minors to effective judicial protection, legal certainty, best interests, and the right to defense, based on the understanding that “hearing the minor” implies paying sufficient attention, understanding their expressions, gestures, and words.